Combining Student Choice of Reading Passage with a Repeated Reading Intervention to Increase Oral Reading Fluency - Danes, Karissa E. (My University, 2013)
Reading skills are critical to student success in school. Unfortunately, approximately I million children in the United States struggle with some aspect of reading during the first three years of school. Without appropriate and early intervention to address reading fluency, a gap in academic performance can develop between a struggling reader and most of his or her peers, and can follow this struggling reader through his or her academic career (Stanovich, I 986). Due to a paradigm shift taking place in the nation's education system, research investigating the effectiveness of various reading instruction techniques and interventions, including interventions targeting reading fluency, is important. One particular intervention that targets reading fluency and is extensively supported in the literature is repeated reading (Therrien, 2004). Educators and educational textbooks suggest that providing students choices is an important part of the learning process. A large body of research also exists concerning the importance oral reading fluency. Although there is evidence of the importance of oral reading fluency in education, and an emphasis in education on allowing students to make choices in the learning process, there is a lack of research investigating the effect of providing a choice of reading passages to readers when attempting to improve oral reading fluency. The purpose of the present study is to address the current gap in the literature and to identity if providing a choice of reading passage within an intervention increases oral reading fluency. The current study involved providing students with a choice between two reading passages in combination with an evidence-based reading fluency intervention: repeated reading. Specifically, the study investigated whether the choice component would substantially improve reading fluency scores as compared to providing the evidencebased intervention without passage choice. Three participants were exposed alternating treatments of a repeated reading intervention and an opportunity to choose between two different passages before completing a repeated reading intervention. No significant differences in mean oral reading fluency scores were found between the two intervention conditions for each participant. However, moderate to significant gains from pre- to post-intervention were made among all participants. Results suggest that providing a choice of reading passage did not increase oral reading fluency scores among these particular students, but did provide evidence in support of the efficacy of the repeated reading intervention.
Thesis (Educational Specialist in School Psychology)
Keywords: Oral reading--Psychological aspects; Choice (Psychology)--Educational aspects; Fluency (Language learning); Reading (Primary)--Remedial teaching; Response to intervention (Learning disabled children); Reading, Psychology of